Arbuscular mycorrhizal fungi alleviate Mn phytotoxicity by altering Mn subcellular distribution and chemical forms in Lespedeza davidii - Pan, Gao; Hu, Jiayao; Zi, Zhen; Wang, Wenying; Li, Xinhang; Xu, Xiaoli; Liu, Wensheng (Frontiers in Plant Science, 2024)
Introduction Arbuscular mycorrhizal fungi (AMF) can relieve manganese (Mn) phytotoxicity and promote plant growth under Mn stress, but their roles remain unclear. Methods In this study, Lespedeza davidii inoculated with or without AMF (Glomus mosseae) under different Mn concentrations (0 mmol/L, 1 mmol/L, 5 mmol/L, 10 mmol/L, and 20 mmol/L) was cultivated via a pot experiment, and plant biomass, physiological and biochemical characteristics, manganese absorption, subcellular distribution, and chemical forms of Mn were examined. Results The results showed that root biomass, stem biomass, leaf biomass, and total individual biomass decreased under high Mn concentrations (above 10 mmol/L), and the inoculated plants had higher biomass than the uninoculated plants. With the increasing Mn concentration, the contents of soluble sugar, soluble protein, free proline, superoxide dismutase (SOD), peroxidase (POD), and catalase (CAT) increased first and then decreased, while the malondialdehyde (MDA) content increased. The contents of soluble sugar, soluble protein, free proline, SOD, POD, and CAT in the inoculated group were higher than those in the uninoculated group at the Mn concentration of 20 mmol/L. The content of MDA in the inoculated plants was lower than that in the uninoculated plants. AMF inoculation enriched most of the manganese in the root system when compared with the non-mycorrhizal treatment. Subcellular distribution of Mn indicated that most of the Mn ions were stored in the cell wall and the vacuoles (the soluble fractions), and the proportion of Mn content in the cell wall components and the vacuole components in leaves in the inoculated group was higher than that in the uninoculated group. Furthermore, the proportions of Mn extracted using ethanol and deionized water in the uninoculated group in stems and roots were higher than those in the inoculated group, which suggested that AMF could convert Mn into inactive forms. Discussion The present study demonstrated that AMF could improve the resistance of L. davidii to Mn toxicity by increasing the activity of antioxidant enzymes and altering the subcellular distribution and chemical forms of Mn.